2019
DOI: 10.3233/jad-180857
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Proxy- or Self-Reported Cognitive Decline and Cognitive Performance in Memory Clinic Visitors

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…This study may contribute to a better understanding of this association. Indeed, informant reports of worse cognition is related to incident dementia (Gruters et al, 2019). It is possible that the detection of cognitive decline by a knowledgeable informant may be an intermediate phase in the conversion to cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This study may contribute to a better understanding of this association. Indeed, informant reports of worse cognition is related to incident dementia (Gruters et al, 2019). It is possible that the detection of cognitive decline by a knowledgeable informant may be an intermediate phase in the conversion to cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of correlation between objective cognitive performance and subjective cognitive complaints is not specific for Lyme, but has been demonstrated in other disorders as well (including HIV, dementia, and rheumatoid arthritis) [2830]. Subjective cognitive complaints are often associated with depressive symptoms [29]. The percentage of 2.9% cognitively impaired patients is comparable to what is found in the normal population (i.e., by definition 2.3% of a normative sample performs worse than 2 SD below the normative mean).…”
Section: Discussionmentioning
confidence: 99%
“…As such, informants play a critical role in diagnosis and have been found to help distinguish between preclinical AD and normal aging [11]. In fact, several studies have found that informantrated cognition is a better predictor of cognitive impairment outcomes than self-reported cognition [12][13][14]. Rabin and colleagues, for example, found that informant reports provided incremental predictive power beyond episodic memory for risk of AD, whereas self-reported cognition did not [12].…”
mentioning
confidence: 99%
“…Rabin and colleagues, for example, found that informant reports provided incremental predictive power beyond episodic memory for risk of AD, whereas self-reported cognition did not [12]. Gruters and colleagues likewise found that informant-rated cognitive decline, but not self-rated decline, was a predictor of incident dementia [14]. Compared to self-reports, informants may be able to better detect changes in cognition that are indicative of pathological changes.…”
mentioning
confidence: 99%